DEIKSIS EKSOFORA DAN ENDOFORA PADA KOLOM OPINI JAWA POS EDISI 29 MARET 2017 - Khusnul Khotimah (Universitas 17 Agustus 1945 Surabaya, 2018)
This study discusses the analysis of deixis eksofora and endofora in the Jawa Pos Opinion column, March 29, 2017 edition. Researcher used qualitative methods with the object of research entitled Surrender or Cheating Type by Azrul Ananda. This study uses data documentation collection techniques in the network accessed on April 19, 2017 through Jawa Pos Online page. Data analysis technique used consists of four stages, including data collection phase, data reduction phase, data presentation phase, and conclusion withdrawal phase. The results show that Azrul Ananda in March 29, 2017 edition Opini column exploits the ecotoxid deixis persona, time, and space. The author Azrul Ananda also used the deoption of anaphoric endofora persona or not persona, but did not use the deoption endofora katafora persona or not persona. Keywords: Deixis, Opini column, Jawa Pos